Good Fences Make Good Neighbors: A Longitudinal Analysis of an Industry Self-Regulatory Institution - Barnett, Michael L.; King, Andrew A. (Academy of Management Journal, 2008)
We extend theories of self-regulation of physical commons to analyze self-regulation of intangible commons in modern industry. We posit that when the action of one firm can cause “spillover” harm to others, firms share a type of commons. We theorize that the need to protect this commons can motivate the formation of a self-regulatory institution. Using data from the U.S. chemical industry, we find that spillover harm from industrial accidents increased after a major industry crisis and decreased following the formation of a new institution. Additionally, our findings suggest that the institution lessened spillovers from participants to the broader industry.